3D modelling of offshore alluvial tin mineralization in Ringarooma Bay, Tasmania - Campbell McKenzie; Alexandra Miller; Michelle Stokes (Society for Mining, Metallurgy & Exploration, 2014)
"The ancestral Ringarooma River in northeast Tasmania has transported alluvial tin and other heavy minerals from their onshore source of stanniferous Devonian granites downstream into what is now Ringarooma Bay. Previous exploration work has demonstrated the presence of potentially economic tin mineralisation within the palaeochannels and terraces associated with the submerged river.The offshore tin resource lies directly on the seabed or with less than 2 m of overburden, and within 5 - 50 m water depths in the wider bay area. The main river channel continues offshore for at least 13 km, with high tin grades found within the palaeochannel but also dispersed across the sea floor as a sheet wash, a result of Quaternary sea level change reworking the placer deposits. This drowned portion of the coastal plain contains a continuation of rich tin leads as low gradient anastomosing channels, and has been delineated by marine seismic and drilling activity since the 1960s. Tin grades in the Tertiary and Quaternary alluvial profiles vary from 50 - 300 g/m3, with the highest concentrations in the coarser basal horizons. A previous offshore explorer estimated a resource of 194 Mm3 at 150 - 250 g/m3.Kenex Ltd created 3D models of the paleochannels and the mineralisation with the aim of better constraining the resource estimate and identifying additional depositional areas. The modelling was undertaken with the input of geophysical data, bathymetry and geochemical sampling of the seabed surface and from historic offshore drill holes. A prospectivity model covering Ringarooma Bay was produced to target tin-bearing gravels. Predictive maps were created to represent various features of the offshore mineral system, including assessing gradient changes in palaeochannels and their sinuosity. The model identifies areas with higher potential for alluvial tin mineralisation and will be used to focus the exploration programme over tenements currently held by Kenex Ltd."